Analysis of Flavonoid Levels in Tin (Ficus carica Linn) Fruit - Rahmasita Rahmasita; Siti Nuryanti; Supriadi Supriadi (Universitas Tadulako, 2021)
Tin fruit is an essential source of bioactive components such as phenol, benzaldehyde, and flavonoids due to the antioxidant properties. Analysis of flavonoid levels on Tin (Ficus carica Linn) fruit was carried out using Uv-Vis spectrophotometry. This study aimed to determine the total flavonoid levels found in Tin (Ficus carica Linn) fruit with a variety of samples of raw, half-ripe, and riped. Extraction of chemical content in Tin (Ficus carica Linn) was carried out by maceration method with ethanol 70%. Total flavonoid levels of the extracts sample were determined through absorption measurements at a wavelength of 520 nm and 700 nm. The results showed that total flavonoid levels in raw, half-ripe, and ripe fruits are 5.778 × 103, 3.056 × 103, and 3.707 × 103 mg/L, respectively, or equivalent to 17334 × 103, 9.168 × 103, and 11.121 × 103 mg/100g, respectively.